2019
DOI: 10.2147/copd.s196109
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical phenotypes of COPD and health-related quality of life: a cross-sectional study</p>

Abstract: Introduction The Spanish COPD guideline (GesEPOC) classifies COPD into four clinical phenotypes based on the exacerbation frequency and dominant clinical manifestations. In this study, we compared the disease-specific health-related quality of life (HRQoL) of patients with different clinical phenotypes. Methods This was a cross-sectional study of patients with COPD attending the respiratory medicine clinic of University of Malaya Medical Centre from 1 June 2017 to 31 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 37 publications
4
52
0
1
Order By: Relevance
“…8849 patients from ten studies [9][10][11][12][13][14][15][16][17][18] were included, of which 2699 patients with the FE-CB phenotype and 6150 patients with the NE phenotype. Study characteristics are summarized in Table 1.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…8849 patients from ten studies [9][10][11][12][13][14][15][16][17][18] were included, of which 2699 patients with the FE-CB phenotype and 6150 patients with the NE phenotype. Study characteristics are summarized in Table 1.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Ten studies [9][10][11][12][13][14][15][16][17][18] reported FEV 1 %pred of COPD patients with the FE-CB and NE phenotypes. In nine studies [9][10][11][12][13][14][15][16][17] , the FEV 1 %pred of the FE-CB phenotype was significantly lower than that of the NE phenotype, while one other study [18] found no significant between-group difference in this respect. Owing to significant heterogeneity among the studies, the random-effects model was used for analysis.…”
Section: Fev 1 %Predmentioning
confidence: 99%
See 3 more Smart Citations